Tal pai tal filho: impalatabilidade de larvas de Phyllomedusa bahiana (Phyllomedusidae: Anura), como defesa anti-predação - Mendes, Josemar da Silva (2018)
The features developed on an organism that reduces the probability of being attacked and killed by predators may be considered a defensive mechanism, which are important attributes for the survival of individuals. In anuran amphibians, the defense strategies involve specific morphological, physiological and behavioral adaptations, besides pattern color. In tadpoles, defense strategies can be related with the development stage. Besides, defense behavior can be induced by recognition of warning signs produced and released by tadpoles during a predation event, or also by chemical substances released by predators in the environment. The impalatibility of tadpoles of some species can be influenced by the stage of ontogenetic development and intensify as the individual approaches its final phase of metamorphosis. Our study tested which anti-predatory strategies can be found in P. bahiana tadpoles during the ontogenetic development. We verified: (i) if P. bahiana tadpoles will exhibit behavioral changes when subjected to a chemical signal from the predator, ii) if more advanced stages of larval development influence positively the impalatability, through the appearance of secretory glands of toxic substances of P. bahiana tadpoles, and (iii) if predators of chewing type oral devices (odonata naiades) reject tadpoles of P. bahiana when in the presence of tadpoles of Scinax x-signatus. Our results confirmed that there is a reduction in swimming activity of P. bahiana tadpoles when subjected to the chemical predator signal and that odonata larvae avoid feeding on P. bahiana tadpoles at more advanced stages of ontogenetic development (38-41). The predators preferred the tadpoles of Scinax x-signatus to P. bahiana tadpoles at all stages of development. This result indicates that tadpoles of this species are unpalatable to this predator. This impalatability of P. bahiana may be present from early stages of tadpoles, which results in the possible co-occurrence of this species in environments with odonata larvae. Respabilities antipredatórias in the cannabis of P. bahiana, cannon on the canisters of diretas and directas deixada pelo predador no meio ambiente, e ao desenvolvimento ontogenético do girino.